A Critical Review on Understanding and Management of Gestational Hypertension - In Ayurveda. - Kulkarni, Kshama (International Research Journal of Ayurveda & Yoga, 2022)
The journey of pregnancy is most exciting and filled with joyous in a women’s life. It’s a gift to every woman of creation and nurturing power. Hypertensive disorders of pregnancy is one of the common complication observed during pregnancy, plays a significant role in maternal and fetal morbidity and mortality. Garbhajanyavishamayata (Pregnancy induced hypertension) is the development of new hypertension in pregnant women after 20 weeks of gestation. They are preventable by early detection and with appropriate treatment and possibly by prevention of disease itself. Ayurveda can definitely contribute in this regard and ensures safe motherhood and healthy child. With an Ayurvedic approach, on looking to the symptoms and understanding etiopathogenesis, Vata dusti is main causative factor in the manifestation of the disease. During progressive stage of disease involvement of other Dosha is seen. Dushya are Hridaya, Dashdhamanya, Sira, Rasa-Raktvahastrotasa, Manovahastrotasa, Rasadhatu, Raktadhatu and Mana, treatment should always be Vatashaman, Pittashamana, Hridya, Shothahara, Garbhasthapaka, Medhya, Brahman, Raktashaman, Balya, Anulomana. As a preventive care, Pathyapathya during Antenatal period is described under the heading of Masanumasika paricharya & what should be avoided is mentioned under the heading of Garbhopaghatakara bhava’s. All these regimens were sincerely followed at that time.